Review of Intervening Variables in Increasing Earnings Per Share - Hasanuddin; Deby Rita Karundeng; Mohamad Taufik Hiola; Novaliastuti Masiaga; Idrus Usu; Badaruddin; Mulyana Machmud (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The COVID-19 pandemic disrupted global economies, impacting financial performance and investor confidence in the Indonesian property and real estate sector. This study aims to evaluate the influence of Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM) on Earnings Per Share (EPS), with Return on Equity (ROE) as an intervening variable. Using path analysis via SmartPLS 3, the study analyzes secondary data from financial statements of 90 property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2021. The findings reveal that NPM, TATO, and EM significantly affect ROE, with EM showing the strongest impact due to high leverage. However, NPM and TATO have insignificant direct effects on EPS, while EM significantly influences EPS. ROE strongly mediates the effects of NPM, TATO, and EM on EPS, confirming its role as a critical mediator. These results underscore the importance of balanced leverage and efficient asset utilization for sustaining profitability, offering insights for investors and managers navigating volatile markets.